Exploring room- and low-temperature performance of hard carbon material in half and full Na-ion batteries. (1st September 2019) - Lin, Xiuyi; Du, Xiaoqiong; Tsui, Pui Shing; Huang, Jian-Qiu; Tan, Hong; Zhang, Biao
Abstract: Being abundant in nature, biomass is the most attractive precursors of hard carbon (HC) anodes for Na-ion batteries (NIBs). The complexity of precursor has discouraged the development of a benchmark in synthesizing biomass-derived HC. Using longan peel as a model material, a facile two-step thermal treatment is proposed to avoid the self-activation, resulting in the HC with appropriate surface area and pore size distribution. A reversible capacity of 309 mAh g −1 is delivered with an initial Coulombic efficiency of 80%. As-prepared HC is further investigated at −20 °C to shed insights into the low temperature behavior of NIB for practical application. In/ex situ XRD and Raman spectroscopy are conducted, exhibiting a safe and reversible capacity of 250 mAh g −1 without Na plating at −20 °C for HC. The full cell consists of HC/Na3.5 V2 (PO4 )2 F3 is also examined. An energy density of 310 Wh kg −1 with an average discharge potential of 3.62 V is achieved at 25 °C, whereas the formation of unstable SEI at low temperature leads to the capacity fading of the full cell at −20 °C. This finding reports a low-cost and high energy density NIB, and unveil the critical challenge of using HC for the low-temperature application.